Cyclic dipeptide, furan, furanone, and butenolide derivatives from marine-derived fungus Aspergillus sp. HL24: Cyclic dipeptide, furan, furanone, and butenolide derivatives from marine-derived fungus Aspergillus sp. HL24 - Ngoc, Ninh Thi; Vien, Le Thi; Cham, Pham Thi; Hanh, Tran Thi Hong; Ninh, Khac Thanh Tung; Thao, Do Thi; Cuong, Nguyen Xuan; Nam, Nguyen Hoai (Vietnam Journal of Marine Science and Technology, 2025)
Using various chromatographic experiments, one cyclic dipeptide (1), one furan (2), one pyranone (3) and two butenolide (4 and 5) derivatives were isolated from the marine-derived fungus Aspergillus sp. HL24. Their chemical structures were elucidated on the basis of detailed analysis of the 1D (1H NMR and 13C NMR) and 2D (HSQC and HMBC) NMR spectroscopic data in comparison with the literature values. The cytotoxic activities of compounds 1–5 were evaluated on two human cancer cell lines as Hep-G2 (liver) and A549 (lung). However, these compounds did not show significant cytotoxicity (IC50 > 100 µM) against both cell lines.